2022
DOI: 10.1093/humrep/deac175
|View full text |Cite
|
Sign up to set email alerts
|

Human blastocyst spontaneous collapse is associated with worse morphological quality and higher degeneration and aneuploidy rates: a comprehensive analysis standardized through artificial intelligence

Abstract: STUDY QUESTION What are the factors associated with human blastocyst spontaneous collapse and the consequences of this event? SUMMARY ANSWER Approximately 50% of blastocysts collapsed, especially when non-viable, morphologically poor and/or aneuploid. WHAT IS KNOWN ALREADY Time-lapse microscopy (TLM) is a powerful tool to observe preimplantation development d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 60 publications
1
39
0
Order By: Relevance
“…To date, there are few studies showing the benefits of using AI in the observation and evaluation of human embryo preimplantation dynamics. 48 , 75 , 76 , 77 By establishing valid and effective algorithms for time‐lapse incubators, we will be able to set stronger criteria that will qualify the prediction of normal growth and development potential of embryos, as well as the detection of aneuploidies, in order to avoid the application of invasive techniques such as preimplantation genetic testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there are few studies showing the benefits of using AI in the observation and evaluation of human embryo preimplantation dynamics. 48 , 75 , 76 , 77 By establishing valid and effective algorithms for time‐lapse incubators, we will be able to set stronger criteria that will qualify the prediction of normal growth and development potential of embryos, as well as the detection of aneuploidies, in order to avoid the application of invasive techniques such as preimplantation genetic testing.…”
Section: Discussionmentioning
confidence: 99%
“…However, spontaneous blastocoel collapse is generally considered to have a negative effect on embryonic development by the observation of hR‐TLC. 4 , 48 It has been confirmed that blastocysts with repeated major collapses have a high probability of poor subsequent development, failure to reach hatching and a lower live birth rate. Nevertheless, the blastocyst multiple collapse pattern is not recommended to be evaluated alone as a predictor of the reproductive outcome, but the morphokinetic variables should also be taken into account.…”
Section: Main Findingsmentioning
confidence: 98%
“…There are, however, alternative paths to address the transferability issue by utilizing more transferable qualitative TLV measures, such as abnormal cleavage ( Liu et al , 2020a ) or spontaneous blastocyst collapse ( Bickendorf et al , 2023 ). Annotation for embryo abnormal cleavage patterns is still mostly performed manually by an embryologist, while newer reports, such as on blastocyst spontaneous collapse ( Cimadomo et al , 2022 ), are starting to engage AI-powered tools to enable automated annotation. In fact, automated annotation is worth further attention considering its important role in both improvement of consistency and accuracy in annotating time-lapse images and maintaining better interpretability of embryo selection.…”
Section: Ai-driven Dsssmentioning
confidence: 99%
“…This progress, however, has purely focused on the annotation aspect without involving any ranking step. More recently, Cimadomo et al (2022) investigated blastocyst collapsing events in much detail by annotating start/end times of blastocyst collapse as well as the degree of blastocoel shrinkage. This study underlined blastocyst collapsing as a potential viability marker.…”
Section: Ai-driven Dsssmentioning
confidence: 99%
“…It is well known that the rate of aneuploid embryos increases dramatically with maternal age [ 3 ]. Several studies have assessed the relationship between embryo euploidy rates and ovarian stimulation process, culture conditions or the morphological features of blastocyst [ 4 6 ]. Although entire chromosomal aneuploidy in embryo originates mainly from meiotic errors during oocyte generation, approximately 8.1% of aneuploid embryos are still paternal in origin [ 7 ].…”
Section: Introductionmentioning
confidence: 99%